2021
DOI: 10.1038/s41598-021-00166-0
|View full text |Cite
|
Sign up to set email alerts
|

Public toilets with insufficient ventilation present high cross infection risk

Abstract: Due to insufficient ventilation, public toilets present high risks for cross-infection. The study investigated 61 public toilets to identify the causes and locations of biological contaminated sources. Airborne and surface bacterial contamination, carbon dioxide concentration, and surface ammonia levels were measured. Both bacterial contamination and CO2 are higher in non-ventilated toilets compared to their ventilated counterparts. Bacteria colony forming units (CFUs) in a public toilet with poor ventilation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…15 The 10 mandibular molar-removing forceps that were disinfected with ozonized water had a mean bacterial count of 4.00 AE 4.32 CFU/mL, showing they were still contaminated with pathogenic microorganisms with the highest number of bacterial colonies being 11Á10 3 CFU/mL. 16 The 10 forceps which were disinfected with 4.8% chloroxylenol had a mean bacterial count of 16.00 AE 6.65 CFU/mL, showing they were still contaminated with pathogenic microorganisms, with the highest number of bacterial colonies being 27Á10 3 CFU/mL. 17 Meanwhile, the mean bacterial count in the negative control group (Aquades) the 10 pliers extracting mandibular molars showed 217.50 AE 39.24 CFU/mL still forming bacterial colonies, with the highest number of bacterial colonies being 292 Á 10 3 CFU/mL (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…15 The 10 mandibular molar-removing forceps that were disinfected with ozonized water had a mean bacterial count of 4.00 AE 4.32 CFU/mL, showing they were still contaminated with pathogenic microorganisms with the highest number of bacterial colonies being 11Á10 3 CFU/mL. 16 The 10 forceps which were disinfected with 4.8% chloroxylenol had a mean bacterial count of 16.00 AE 6.65 CFU/mL, showing they were still contaminated with pathogenic microorganisms, with the highest number of bacterial colonies being 27Á10 3 CFU/mL. 17 Meanwhile, the mean bacterial count in the negative control group (Aquades) the 10 pliers extracting mandibular molars showed 217.50 AE 39.24 CFU/mL still forming bacterial colonies, with the highest number of bacterial colonies being 292 Á 10 3 CFU/mL (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Effective ventilation systems can improve indoor air quality [17][18][19] and reduce the spread of viruses [20,21]. Lee et al [22] investigated 61 public toilets and recommended that ventilation and cleaning should be improved to mitigate the risk of cross infection in public toilets. The ventilation rate should be strongly based on the strength of the pollutant sources [23], and higher ventilation rates reduce odor dispersion [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The transmission model by simulating the chain of infection from stool showed E. coli can be transferred via the toilet brush and the door handle to the gloved hand ( Gerhardts et al, 2012 ). In addition, a study of public restrooms in Taiwan showed areas near toilet bowls, squat toilets, and urinals were highly contaminated ( Lee and Tham, 2021 ). Bacteria of potential fecal origin may contaminate human hands, and hand washing can reduce the presence of bacteria ( Judah et al, 2010 ; Burton et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%